Experimental study on performance of pneumatic seeding system - Lijing, Liu; Hui, Yang; Shaochun, Ma (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: The purpose of this study was to promote the development of large-scale agricultural machines in China and meet the demand of air seeder localization. This study investigated the relationship between the working parameters and the performance of pneumatic seeding system, Cangmai 6004 wheat seed was used. A test platform for pneumatic seeding systems was developed, and then a series of experiments were performed based on the quadratic general rotary unitized design and response surface methodology (RSM). The seeding rate and the air flow rate were selected as affecting factors, coefficient of variation (CV) of evenness of feeding rate between rows and CV of seeding stability of total rows were assigned as the test indexes. Regression models between factors and indexes were established, and finally, an optimal equation based on this pneumatic seeding system were established as well, which can determine the proper air flow rate once the seeding rate was set based on the practical agronomic requirements. For example, when the seeding rate is set as 250 kg/hm2 , the proper air flow rate of 7.53 m3/min can be obtained. The verification experiment results showed that the predicted working parameters obtained by RSM were feasible, which might provide a theoretical basis for further research of pneumatic seed metering systems.Keywords: pneumatic seeding system, seeding rate, air flow rate, quadratic general rotary unitized design, regression modelDOI: 10.3965/j.ijabe.20160906.2129Citation: Liu L J, Yang H, Ma S C. Experimental study on performance of pneumatic seeding system. Int J Agric & Biol Eng, 2016; 9(6): 84－90.